TRENDS IN ANTIBIOTIC SUSCEPTIBILITY PATTERNS OF STREPTOCOCCUS PNEUMONIAE AND HAEMOPHILUS INFLUENZAE ISOLATES: FOUR YEARS FOLLOW UP - (:unkn) unknown (ANKARA MICROBIOLOGY SOC, 2010)
This study was aimed to follow up the antibiotic resistance trends in Streptococcus pneumoniae and Haemophilus influenzae isolated from clinical specimens between 2003-2006 at Marmara University Hospital, Istanbul, Turkey Antibiotic susceptibilities were performed by disk diffusion method, and penicillin susceptibility was determined by E-test (AB Biodisk, Sweden) Results were evaluated by CLSI standards During this period a total of 258 S pneumoniae and 548 H influenzae were isolated in our laboratory According to the 2006 CLSI penicillin breakpoints, overall resistance of S pneumoniae isolates to penicillin was 39 9% and intermediate and high level penicillin resistance rates were 30 2% and 9 7%, respectively The rates of high level penicillin resistant pneumococci by years were 11 1% in 2003, 10.9% in 2004, 6% in 2005, 12 1% in 2006 and except for 2005 no significant change in resistance rates was detected However, according to the 2008 CLSI penicillin breakpoints, resistance was found to be 3.5%, intermediate and high level penicillin resistance being 3.1% and 0.4%, respectively. While penicillin resistance rates by years were as 4 4% in 2003, 5.5% in 2004, 0% in 2005 and 4 4% in 2006, high level penicillin resistance was detected only in 2003 as 2 2%. Resistance rates of chloramphenicol, erythromycin, tetracyline and trimethoprim-sulphametoxazole (TMP-SMX) were detected as 10.1%, 19%, 26.8% and 49 2%, respectively while erythromycin, tetracycline and TMP-SMX multi-drug resistance was detected in 12 4% of the isolates. No resistance was detected to vancomycin. Beta-lactamase production rate in H influenzae isolates was 3 3%, being 1 6% in 2003 with a raise up to 4% in 2006 No beta-lactamase negative ampicillin-resistant isolate was detected. Although chloramphenicol and cefaclor resistance were in low levels (2 2% and 0 7%, respectively), TMP-SMX resistance was detected as 25.5% TMP-SMX resistance was two fold more in beta-lactamase producers compared with the non-producers, whereas chloramphenicol resistance revealed a significant increase in beta-lactamase producers (1% versus 44 5%) In conclusion, doubling of beta-lactamase production rate in H.influenzae within years indicates the importance of continuous follow-up of antibiotic resistance in specific pathogens The evaluation of penicillin results obtained for pneumococci according to modified 2008 CLSI criteria revealed that penicillin can still be used effectively in the treatment of pneumococcal respiratory tract infections. Continuous active surveillance of resistance rates provides important data for the determination of the empirical therapy protocols for S pneumoniae and H influenzae infections.
Keywords: Streptococcus pneumoniae; Haemophilus influenzae; penicilin resistance; antibiotic susceptibility; MORAXELLA-CATARRHALIS; ANTIMICROBIAL RESISTANCE; ALEXANDER PROJECT; TURKEY; SURVEILLANCE; MULTICENTER; PATHOGENS